Perancangan Aplikasi Belajar dan Bermain Berbasis Android Untuk Anak Usia Dini Menggunakan Metode UCD (User Centered Design) - Kartina, Riza (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Technological developments are very rapid and have had quite a big impact in various fields, including education. Education is a learning process obtained by every human being, in this case, students; the aim is to make students understand, comprehend, and think more critically. Education can be formulated as guidance for human growth from birth until physical and spiritual maturity is achieved in the interaction of nature and the social environment. Education is a continuous process; it does not stop. Education is the most important thing in our lives because, with education, humans can be helped to survive and solve problems. And being an educated person is very important. The first education we get is from the family, school, and community environments. Early childhood is a golden age for children to accept and capture new things. The method used by researchers in this research is descriptive with a qualitative approach. This research aims to build a learning application that young children can implement. The design and development of this application helps children aged 3-5 years to understand better material about recognizing letters, numbers, fruit, animal colors, shapes, and vehicles. as well as optimizing the function of Android devices owned by parents to be used as educational tools for their children.